Mutations in WNT10A are frequently involved in oligodontia associated with minor signs of ectodermal dysplasia12. Issue 4 (7th February 2013) - Plaisancié, Julie; Bailleul‐Forestier, Isabelle; Gaston, Véronique; Vaysse, Fréderic; Lacombe, Didier; Holder‐Espinasse, Muriel; Abramowicz, Marc; Coubes, Christine; Plessis, Ghislaine; Faivre, Laurence; Demeer, Bénédicte; Vincent‐Delorme, Catherine; et al.
Abstract Ectodermal dysplasias (ED) are a clinically and genetically heterogeneous group of hereditary disorders that have in common abnormal development of ectodermal derivatives. Hypohidrotic ectodermal dysplasia (HED) is characterized by abnormal development of eccrine sweat glands, hair, and teeth. The X‐linked form of the disease, caused by mutations in the EDA gene, represents the majority of patients with the hypohidrotic form. Autosomal dominant and autosomal recessive forms are occasionally seen, and result from mutations in at least three genes (WNT10A, EDAR, or more rarely EDARADD). We have screened for mutations in EDAR (commonly involved in the hypohidrotic form) and WNT10A (involved in a wide spectrum of ED and in isolated hypodontia) in a cohort of 36 patients referred for EDA molecular screening, which failed to identify any mutation. We identified eight EDAR mutations in five patients (two with homozygous mutations, one with compound heterozygous mutations, and two with heterozygous mutation), four of which were novel variants. We identified 28 WNT10A mutations in 16 patients (5 with homozygous mutations, 7 with compound heterozygous mutations, and 4 with heterozygous mutations), seven of which were novel variants. Our study allows a more precise definition of the phenotypic spectrum associated with EDAR and WNT10A mutations and underlines the importance of the implication of WNT10A among patients with ED. © 2013 Wiley Periodicals, Inc.